MATEC Web of Conferences - Popova, E. S. (EDP Sciences, 2018)
A universal method of processing low-grade coals, as well as energy waste, is their gasification. A mathematical model of the conversion of coke, placed in a cylindrical capsule, through which a steam-oxygen blow is carried out, is considered. The determining parameter is the proportion of oxygen in the oxidizer. The values of the oxygen concentration in a steam-oxygen oxidizer are found to produce a synthesis gas with a predetermined percentage of combustible components.